PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, DISIPLIN KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA GURU - Hulmawiyah Hulmawiyah; Lilik Sri Hariani; Udik Yudiono (Jurnal Riset Pendidikan Ekonomi, 2018)
The purpose of this study was to analyze the influence of school principal leadership, work discipline, and compensation to the job satisfaction of teachers of the 10th Vocational High School (SMK) Malang. This research is a type of quantitative research with ex post facto approach. The population in this study were all teachers of State Vocational High School (SMK) 10 Malang, totaling 78 teachers. Sampling uses saturated sample techniques so that all populations are sampled. Data collection techniques using a questionnaire or questionnaire. Data analysis techniques used are descriptive analysis techniques and multiple linear regression analysis with the help of a computer program SPSS 16.00 for Windows. The results of the data analysis showed that the leadership of the school principal, work discipline, and compensation had a positive effect on job satisfaction of teachers of the State Vocational High School (SMK) 10 Malang both simultaneously and partially. Principal leadership, work discipline, and compensation have an effect of 49.3% on the job satisfaction of teachers of the 10th Vocational High School (SMK) Malang, while 50.7% is influenced by other variables not examined, such as: work environment, organizational culture work motivation, work stress, etc.